Pinoresinol reductase 1 impacts lignin distribution during secondary cell wall biosynthesis in Arabidopsis. (April 2015) - Zhao, Qiao; Zeng, Yining; Yin, Yanbin; Pu, Yunqiao; Jackson, Lisa A.; Engle, Nancy L.; Martin, Madhavi Z.; Tschaplinski, Timothy J.; Ding, Shi-You; Ragauskas, Arthur J.; Dixon, Richard A.
Graphical abstract: Loss of function of the gene encoding pinoresinol reductase 1, which is co-expressed with cell wall biosynthetic genes in Arabidopsis thaliana, not only impairs accumulation of lignans in stem tissue, but also alters lignin structure and reduces accumulation of lignin, particularly in interfascicular fibers. Highlights: Pinoresinol reductase 1 (PrR1) is co-expressed with secondary cell wall genes in Arabidopsis. Loss of function of PrR1 results in reductions in the levels of both lignans and lignin. The lignin reduction in the prr1 mutant is mainly in the interfascicular fibers. No other cell wall genes are directly affected in PrR1 loss- or gain-of-function lines. Abstract: Pinoresinol reductase (PrR) catalyzes the conversion of the lignan (−)-pinoresinol to (−)-lariciresinol in Arabidopsis thaliana, where it is encoded by two genes, PrR1 and PrR2, that appear to act redundantly. PrR1 is highly expressed in lignified inflorescence stem tissue, whereas PrR2 expression is barely detectable in stems. Co-expression analysis has indicated that PrR1 is co-expressed with many characterized genes involved in secondary cell wall biosynthesis, whereas PrR2 expression clusters with a different set of genes. The promoter of the PrR1 gene is regulated by the secondary cell wall related transcription factors SND1 and MYB46. The loss-of-function mutant of PrR1 shows, in addition to elevated levels of pinoresinol, significantly decreased lignin content and a slightly altered lignin structure with lower abundance of cinnamyl alcohol end groups. Stimulated Raman scattering (SRS) microscopy analysis indicated that the lignin content of the prr1-1 loss-of-function mutant is similar to that of wild-type plants in xylem cells, which exhibit a normal phenotype, but is reduced in the fiber cells. Together, these data suggest an association of the lignan biosynthetic enzyme encoded by PrR1 with secondary cell wall biosynthesis in fiber cells.